Rancang Bangun CNC Router 3 Axis Ukir Kayu Untuk Kerajinan Kaligrafi - Dwi Riyanto, Sugeng; Yusuf, Muhamad; Dewi, Riyani Prima; Nurdiansyah, Robbihim (Infotekmesin, 2024)
The Indonesian wood industry is diverse, with wood carving being one of its most popular products. However, the manual wood carving process is not suitable for large-scale production. To address this challenge, a new tool has been developed to increase the production of wood crafts, especially calligraphy carving. This tool is a 3-axis wood carving CNC router machine controlled by a computer and smartphone. The CNC router machine was designed using the CNC Shield V3 and the Arduino Uno R3 motor driver, A4988 as a stepper motor controller. The mechanism applied includes creating vector images programmed with gcode, controlling and engraving calligraphy through software on computers and applications on smartphones with Bluetooth HC – 05 communication with a maximum distance of smaller than 10 meters. Based on control data by computer testing geometry testing circle dimensions of 58 mm x 56 mm and feed rates of 5 mm/sec, 8 mm/sec and 10 mm/sec with engraving times of 01:12, 00:48 and 00:42. Testing Muhammad's carving with dimensions of 100 mm x 100 mm and feed rates of 5 mm/sec, 8 mm/sec and 10 mm/sec with engraving times of 05:22, 03:45 and 03:24. Tests for cutting 12 mm thick MDF wood with a depth 1.5 mm and a feed rate of 5 mm/sec cuts 8 rounds for 13:12 min/sec. The control data by smartphone testing the geometry of the circle with dimensions of 50 mm x 50 mm and a feed rate of 500mm/min with a carving time of 58:43 minutes. Testing Muhammad's engraving dimensions of 70mm x 60mm and feed rates of 500 mm/min, 800 mm/min, and 1000 mm/min with engraving times of 54:34, 39:25, and 35:28. The test for cutting 12 mm thick MDF wood with a depth of 1.5 mm and a feed rate of 500 mm/min-cut 8x rounds for 10:21 minutes/second.